Thermoelastic damping analysis of FG Mindlin microplates using strain gradient theory. Issue 12 (1st December 2016) - Emami, A. A.; Alibeigloo, A.
ABSTRACT: Based on Mindlin plate theory, thermoelastic damping (TED) analysis of functionally graded microplates are performed using strain gradient theory. System of governing differential equations coupled with thermal effects and the corresponding boundary conditions are derived using Hamiltonian's principle. Afterward, temperature gradient is obtained by solving the heat conduction equation analytically. Then, the free vibration problem is analyzed to achieve the natural frequencies and quality factor due to TED. The results indicate that the effect of length-scale parameter on the TED of microplate is significant.